Quantum theory of four-atom reactions using arrangement channel hyperspherical coordinates: Formulation and application to OH+H-2<->H2O+H - Pogrebnya, S; Echave, J; Clary, D (1997)
An arrangement channel hyperspherical coordinate method for performing quantum scattering calculations on four-atom reactions is formulated. This method treats the vibrational and rotational states in different arrangement channels by a close-coupling expansion in nonorthogonal functions. The method is applied to the calculation of state-to-state probabilities for the OH+H2→H2O+H reaction. Good agreement is found with cumulative and state-selected reaction probabilities previously calculated by other methods. The major advantage of this general approach is that the whole S matrix can be obtained in a single calculation. © 1997 American Institute of Physics.